Performance Indicators for Energi Management of Tourism in The Pangururan District Kabupaten Samosir (Talenta Publisher, 2022)
. The Lake Toba area is a national tourist area visited by various tourists both from within and outside the country, and is included in the 88 national tours which are the parent of tourism development in Indonesia. One of the infrastructures that must be considered is the availability of electrical energy sources in the tourist area of ​​Lake Toba. Pangururan District as one of the tourism and administrative areas in the Lake Toba area must have sufficient electrical energy needs and become sustainable tourism. The purpose of this study was to examine the Performance of Tourism Energy Management in Pangururan District, Samosir Regency with an approach to analyzing the level of energy use and conservation, energy management programs, and utilization of renewable energy sources. The research method used is direct field observation and literature study, both theory and supporting documents in the research, which is then analyzed by interpreting the data obtained based on the theory and applicable policies. The results of this study are to identify that the need for electrical energy in the tourist area in the Pangururan sub-district is quite evenly distributed and the need for electrical energy is also met, but in the tourist area in the Pangururan sub-district conservation activities and the use of sustainable energy sources carried out by the government and the tourism business unit are still very low. a little. In addition, this research is expected to be a source of knowledge about Energy Management in the Tourism Sector.